2007
DOI: 10.1002/masy.200750310
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification via Plasma Polymerization of Allylamine for Antibody Immobilization

Abstract: Continuous wave and pulsed plasma polymerization coatings of allylamine were investigated for antibody immobilization as a function of plasma power, monomer pressure and treatment time, and duty cycle. Conditions were optimized by evaluating the surface amine density of plasma polymer coated samples before and after aging in dry ethanol for 3 hrs. In addition, plasma polymer coatings were characterized by contact angle analyzer, a-step, and FT-IR/ATR. The continuous wave plasma polymerization provided amine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…The effect of plasma on the retention of the precursor functional group also depends on the plasma mode. Basarir et al [70] worked on plasma polymerization of allylamine using both CW and pulsed modes. Results showed that pulsed plasma polymerization further increased amine density.…”
Section: Effect On Film's Atomic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of plasma on the retention of the precursor functional group also depends on the plasma mode. Basarir et al [70] worked on plasma polymerization of allylamine using both CW and pulsed modes. Results showed that pulsed plasma polymerization further increased amine density.…”
Section: Effect On Film's Atomic Compositionmentioning
confidence: 99%
“…However, the control of the cross-linking degree is an important factor for the optimization of the plasma polymer film stability and mechanical and thermal properties [72]. Therefore, it is important to evaluate the cross-linking degree in addition to the plasma and polymer film chemistry in order to choose the appropriate power [70,73].…”
Section: Effect On Film's Atomic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomedical applications of allylamine PP were first reported by Muratsugu et al (Muratsugu et al, 1991) in which the F(ab') 2 fragments of antibody proteins were densely immobilized on the surface of allylamine PP. Allylamine PPs were subsequently widely used in biomedical applications (Mahoney et al, 2004;Kurosawa et al, 2002;Basarir et al, 2007;Zhang et al, 2003;Zhang et al, 2005). The PP surfaces of ethylenediamine (EDA) and alkylamines have amino groups and have also been used in biomedical applications (Jung et al, 2006;Nakanishi et al, 1996;.…”
Section: Plasma Polymerization For Biosensor Designmentioning
confidence: 99%
“…This methodology of creating polymers allows adherent and continuous coatings to be formed on a broad range of substrates, including microtiter plates. 24 Plasma polymers have been produced from a diverse range of monomers, including allylamine, 25,26 cyclopropylamine, 27 bromine, 28 polyethylene glycol (PEG), diethylene glycol dimethyl ether (diglyme), [29][30][31] and many others, 32,33 providing a broad spectrum of chemical functionalities for subsequent protein grafting steps, including the option for patterning. [34][35][36] Overall, a significant range of polymers have been used to improve biomolecule immobilization properties of substrates for use in microarray and protein assay applications.…”
mentioning
confidence: 99%